Cosmic gas highways in C-EAGLE simulations - Vurm I.; Nevalainen J.; Hong S.E.; Bahé Y.M.; Dalla Vecchia C.; Heinämäki P. (EDP Sciences, 2025)
Context. A substantial fraction of cosmic baryons is expected to hide in the form of diffuse warm-hot intergalactic medium (WHIM) at X-ray temperatures (T = 105 − 107 K). Due to the expected low density of WHIM, it has been very difficult to detect so far. A statistically significant sample of credible detections of the WHIM phase might help solve the problem of the missing cosmic baryons. While the majority of cosmic gas is approximately at rest inside the filaments of the Cosmic Web, the fraction of gas located close to galaxy clusters is falling towards them with substantial velocities. The infalling gas is influenced by the increasing density in the cluster vicinity and eventually undergoes a termination shock, which may boost its X-ray signal. Thus, the cluster outskirts are potential locations for improved detectability of the missing baryons.
Aims. The primary goal of this work is to identify optimal locations of the enhanced X-ray emission and absorption, arising from the interaction of infalling filamentary gas with cluster material. Our further goal is to improve our understanding of the various physical processes affecting WHIM as it falls towards clusters of galaxies along the cosmic filaments. We aim to utilise this information for planning future X-ray observations of WHIM in cluster outskirts.
Methods. We applied the DisPerSE filament finder to the galaxy distribution in the surroundings of a single Coma-like (M200 ∼ 1015.4 M⊙) simulated C-EAGLE cluster of galaxies. We characterised the distribution of the thermodynamic properties of the gas in such filaments and provided a physical interpretation for the results. This analysis serves as a proof of method to be applied to the full C-EAGLE sample in a future work.
Results. We captured a large fraction (∼50%) of the hot (T >  105.5 K) gas falling towards the cluster in the detected filaments in the cluster outskirts. The gas in the filaments is in approximate free fall all the way down to the radial distance of ∼2 r200 from the cluster. At smaller radii, the filament gas begins to slow down due to the increasing pressure of the ambient gas; approximately half of the filament gas nevertheless penetrates into the cluster before being decelerated. The deceleration is accompanied by the conversion of gas bulk kinetic energy into heat. As a result, the density and temperature of the gas in the filaments increase from the general Cosmic Web level of ρ ∼ 10ρav (where ρav is the cosmic mean baryon density) and T = 105 − 106 K at r ∼ 4 r200 towards ρ ∼ 100ρav and T = 107 − 108 K at the virial boundary of the very massive cluster studied in this paper.
Conclusions. The detection of the cosmic filaments of galaxies around clusters may provide a practical observational avenue for locating the densest and hottest phase of the missing baryons.